TEACHERS’ ROLE IN TEACHING ENGLISH ONLINE CLASSES DURING THE PANDEMIC - Fahranah, Riqah; Atmowardoyo, Haryanto; Samtidar, Samtidar (Universitas Negeri Makassar, 2022)
This study aims to determine the role of teachers in teaching English during the pandemic. This study used the descriptive qualitative method. The research data were collected through interviews. The subjects of this study were English teachers at SMA Negeri 3 Makassar 3 people who had met the criteria determined by the study. The results of the data analysis found that (1) there were several roles used by teachers in teaching online English classes during the pandemic, among others, the teacher as a facilitator, namely providing explanations and examples described through pictures, the teacher as a driver providing support to students to appreciate student learning efforts in the classroom. Then, the teacher, as a model, reminds us to maintain health and provides the material with enthusiasm and confidence. Motivate students in learning English, and control students in the classroom with the rules given by the teacher (2) there are several media or applications that teachers use in teaching online classes during a pandemic, among others, using learning media through videos and pictures and the applications used are Microsoft Teams, Google Meet, and Google Classroom.